Systemically Infused Mesenchymal Stem Cells Show Different Homing Profiles in Healthy and Tumor Mouse Models. (16th February 2017) - Xie, Chengying; Yang, Zhangru; Suo, Yuanzhen; Chen, Qianqian; Wei, Dan; Weng, Xiaofu; Gu, Zhengqin; Wei, Xunbin
Abstract: Bone marrow-derived mesenchymal stem cells (MSCs) can localize in injured, inflamed, and cancerous tissues after systemic infusion. However, the dynamic homing profile of MSCs in the peripheral blood is not well characterized. Here, using in vivo flow cytometry to noninvasively monitor the dynamics of fluorescence-labeled cells, we found different clearance kinetics of systemically infused MSCs between healthy and tumor mouse models. The circulation times of MSCs in healthy mice and mice with subcutaneous tumors, orthotopically transplanted liver tumors, or metastatic lung tumors were 30, 24, 18, and 12 hours, respectively, suggesting that MSCs actively home to tumor environments. MSCs infiltrated into hepatocellular carcinoma (HCC) sites and preferentially engrafted to micrometastatic regions both in vivo and in vitro. The expression of epidermal growth factor, CXCL9, CCL25, and matrix metalloproteinases-9 by HCC cells differed between primary tumor sites and metastatic regions. By characterizing the homing profiles of systemically perfused MSCs under physiological and cancerous conditions, these findings increase our understanding of the migration of MSCs from the circulation to tumor sites and constitute a basis for developing MSC-based anti-cancer therapeutic strategies.